USAHA MENGATASI PROBLEMATIKA PENDIDIKAN SAINS DI SEKOLAH DAN PERGURUAN TINGGI - Milya Sari (AT-TA'LIM, 2012)
Science holds an important role in the age of globalization. Countries that ruled the science will dominate the economy. Indonesia including State lagging in science and technological literacy. A lot of things that cause less maximum learning science during this time. Eleven science education policy issues from Unesco in 2008, all the problems of the science education in Indonesia. The largest factor is the teacher, then the policy leadership and Government. Attempts to overcome this of course relates to the improvement of the quality of teachers and better government policy prioritizing science education